Pengaruh Hukum Adat Batak Sebagai Sumber dalam Hukum Waris di Indonesia - Anugrah Septrianta Sitepu; Jefrizal Shadli Karo-Karo; Rosmalinda Rosmalinda (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
Inheritance law is a law that regulates the transfer of assets left by a deceased person and its consequences for his heirs. Inheritance law is one element of customary law in Indonesia. The patrilineal principle, in which inheritance prioritizes the male lineage, is upheld in Batak inheritance law. According to Batak customary law, men and women are treated differently. The type of research is normative juridical. The data source is a secondary data source. The nature of the research is descriptive analytical. Data collection techniques are literature studies and document studies. Data analysis uses a qualitative approach method. The purpose of this study is to determine the influence of the Batak customary law system as a source of inheritance law in Indonesia, and to determine the implementation of Batak customary law on inheritance law in Indonesia. The inheritance system in Batak society adheres to the Patrilineal Principle. In this principle, the position and influence of men in Batak customary inheritance law are very strong. According to civil law, inheritance is defined as a set of legal provisions that regulate the general legal consequences in the field of property law arising from a person's death. Based on this theory, it can be concluded that the position of Batak boys and girls in the inheritance distribution system and the application of customary law in the distribution of inheritance for boys and girls is in harmony. The Batak Toba customary inheritance law is the basis for the distribution of inheritance in its unique society. Its teachings that include inheritance flowing through the male line are cassation and dakdanak. According to the Batak Toba inheritance law, this uniqueness gives the status of first heir to the eldest son of the family, thus giving him his own identity. The customary inheritance law system in Indonesia generally tends to follow positive legal norms, although the principle of dakdanak emphasizes more on justice in the distribution of inheritance. However, when the legislation on Batak Toba customary inheritance is included in the framework of affirmative legislation, the situation becomes complicated. The principles of positive law that respect women's inheritance rights, especially those related to inheritance of movable property, conflict with the Batak Toba customary law system which automatically inherits property to sons from the paternal line. Positive law attempts to take this understanding into account, but there are still potential problems due to the fundamental differences between the two legal systems that must be resolved.